Modified transanal repair of congenital H-type rectovestibular fistula: A technique to avoid recurrence - Taiwo A Lawal; Aiwanlehi Eighemhenrio; Felix O Kumolalo (Wolters Kluwer Medknow Publications, 2013)
Congenital H-type rectovestibular fistulas are rare in the spectrum of anorectal malformations. Repair is associated with recurrence rates of up to 30%, using perineal repair, vestibuloanal pull-through or anterior anorectoplasty. The rarity of the malformation has limited experience with the surgical approach; hence, the rate of wound breakdown. We describe the use of a modification of the transanal approach for the repair in a 7-month-old female patient.